Multimodal digital tools and EFL audio-visual comprehension: Students' attitudes towards vodcasts - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Natalia Norte Fernández-Pacheco CESA Alicante, Spain   ABSTRACT The emergence of Information and Communication Technologies (ICT) has helped in the development and application of new language teaching materials that promote a multimodal approach (Jewitt, 2009, 2013; Kress and Leeuwen, 2001). Multimodal digital tools, such as vodcasts, bring together diverse modes of communication, which may enhance students' foreign language audio-visual comprehension. This paper discusses a study on the attitudes of 40 Spanish students at a B2 level, aged between 14 and 19, towards the use of vodcasts, in comparison with audio tracks. Questionnaires were employed to gather data on student attitudes towards two British Council vodcasts. The results showed positive attitudes towards the use of multimodal digital tools (e.g., vodcasts) rather than traditional listening activities (e.g., audio tracks). We suggest these findings point to the potential of vodcasts not only as influential multimodal tools to improve EFL students' audio-visual comprehension but also to increase students' enjoyment and engagement when learning English as a foreign language.